Optimizing Dynamic Takt Time In Single Model Assembly Line Balancing Problem Considering Flexible Assignment Using Mathematical Modelling - Montororing, Yuri Delano Regent (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
The pursuit of assembly line balance aims to enhance efficiency by optimizing the ratio between output and input. Achieving balance necessitates meticulous planning to ensure that machines at each workstation operate with equitable workloads. Notably, the assembly line plays a crucial role in this equilibrium. In a manufacturing company, excels in timely product delivery to customers. However, a decline in productivity is attributed to inefficient production processes. The production department operates based on takt time, aligning with customer demand requirements. Despite meeting customer demands promptly, the company usually needs to work on productivity due to fluctuating customer demands and varying process capacities. The consistent use of a capacity production leads to stable productivity and high loss of time due to efficient work hours. Driven by the background, the researcher aims to delve into workstation arrangements for efficient production processes, with the ultimate goal of minimizing wait times, analyzing work hour precision to reduce loss time, and optimizing time usage based on takt time in the production line for efficiency. The study incorporates line-balancing methods to enhance time usage effectiveness in each production line.